Organoleptic Characteristics of Natural Flavour Powder From Waste of Swimming Blue Crabs (Portunus pelagicus ) Processing: Study on Dextrin Concentration and Drying Temperature - Maligan, Jaya Mahar; Wignyanto, Wignyanto; Hermansyah, Ricky; Mulyadi, Arie Febrianto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2013)
As a maritime country, Indonesia has the potential product of marine fisheries are very abundant, but the potential is still not used optimally. One of the potential that can be developed is wimming blue crab. Besides the meat, use the swimming blue crabs shells are also quite large. One use of this shell is used as the main ingredient of natural flavour powder manufacture. Making natural flavour powder from waste of swimming blue crabs meat processing need to consider several factors, among which the concentration of filler material (filler) used the dextrin and drying temperature, therefore it is necessary to do a study of dextrin concentration and drying temperature on the manufacture of powdered natural flavour from waste of swimming crabs meat processing. The best results are at 60 Â°C drying temperature and the concentration of 10% dextrin. The best treatment has a value of organoleptic parameters namely the taste of 2.6 (neutral), aroma of 3 (neutral), color of 3.6 (like), texture of 3.8 (like), and for the physical parameters of the water content of 6%, the solubility of 74.67% and 10.34% absorption.Keywords: Taste, aroma, color, texture, filler